Chromatin dynamics after DNA damage: the legacy of the Access-Repair-Restore model - Polo, Sophie E. (DNA Repair (Amst), 2015)
Eukaryotic genomes are packaged into chromatin, which is the physiological substrate for all DNA transactions, including DNA damage and repair. Chromatin organization imposes major constraints on DNA damage repair and thus undergoes critical rearrangements during the repair process. These rearrangements have been integrated into the “Access-Repair-Restore” (ARR) model, which provides a molecular framework for chromatin dynamics in response to DNA damage. Here, we take a historical perspective on the elaboration of this model and describe the molecular players involved in damaged chromatin reorganization in human cells. In particular, we present our current knowledge of chromatin assembly coupled to DNA damage repair, focusing on the role of histone variants and their dedicated chaperones. Finally, we discuss the impact of chromatin rearrangements after DNA damage on chromatin function and epigenome maintenance.